Language Use: Code Mixing, Code Switching, Borrowing, Pidginization, and Creolization - Komang Trisna Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This study was conducted to gather sufficient information on the language use:code mixing, code switching, borrowing, pidginization, and creolization. The methodused in this study is through a literature study that collects several previous studies toanswer about code mixing, code switching, borrowing, pidginization, and creolizationpurposes. The results of this study that code can be a variety related to the element oflanguage like sentence, clause, phrase and word which have the limitation because thecode which is chosen by the speaker based on his/her necessity in communicating. Code-Mixing is the mix of code from two languages or more in some content of conversation inform of a sentence, while Code-Switching defined as a term which is used to indicateexchange of two or more languages, varieties of language, and can be also an exchange instyle. Moreover, Borrowing is the process of importing linguistic items from one linguisticsystem into another, a process that occurs any time two cultures are in contact over aperiod of time. Furthermore, Pidginization is a simplification of code of language whichhas arisen as the result of contact between people of different languages usually formed amixing of the languages. When pidgin develops to creole, it is described as creolization.Creole is a pidgin which is modified and appropriated in its structure and vocabulary.